Generalized Radical Lifting Modules - Khalid , Wasan; Wadi, Adnan S. (Iraqi Journal of Science, 2022)
In this paper we introduce G-Rad-lifting module as aproper generalization of lifting module, some properties of this type of modules are investigated. We prove that if M is G-Rad- lifting and, then, andare G-Rad- lifting, hence we Conclude the direct summand of G-Rad- lifting is also G-Rad- lifting. Also we prove that if M is a duo module withandare G- Rad- lifting then M is G-Rad- lifting.